2021
DOI: 10.1093/ofid/ofab284
|View full text |Cite
|
Sign up to set email alerts
|

Prior Statin Use and Risk of Mortality and Severe Disease From Coronavirus Disease 2019: A Systematic Review and Meta-analysis

Abstract: Background Statins up-regulate angiotensin converting enzyme-2, the receptor of SARS-CoV-2, while also exhibiting pleiotropic antiviral, antithrombotic and anti-inflammatory properties. Uncertainties exist about their effect on the course of SARS-CoV-2 infection. Objectives We sought to systematically review the literature and perform a meta-analysis to examine the association between prior statins use and outcomes of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
1
4
0
1
Order By: Relevance
“…A meta-analysis of 19 observational studies showed that statins use prior to COVID-19 diagnosis was associated with lower mortality. 31 This aligns with findings observed by Lori et al in which prior use of statins reduced the risk of death in patients with CVD and HTN. 32 Similarly, a multicenter observational study in Italy conducted on 842 patients with COVID-19 failed to demonstrate a statistically significant reduction in mortality among statin users but highlighted that statin use was associated with more severe disease.…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis of 19 observational studies showed that statins use prior to COVID-19 diagnosis was associated with lower mortality. 31 This aligns with findings observed by Lori et al in which prior use of statins reduced the risk of death in patients with CVD and HTN. 32 Similarly, a multicenter observational study in Italy conducted on 842 patients with COVID-19 failed to demonstrate a statistically significant reduction in mortality among statin users but highlighted that statin use was associated with more severe disease.…”
Section: Discussionsupporting
confidence: 90%
“…Statin-associated improved prognosis is partially attributed to the relieved inflammatory response [102]. A number of other researchers have confirmed the beneficial role of statin-use in COVID-19 infection [103][104][105][106][107][108][109][110][111]. Of note, an updated meta-analysis of 22 studies suggested stains use in COVID-19 patients were connected to an approximately 35% decrease in the adjusted risk of mortality [112].…”
Section: Cholesterol Metabolismmentioning
confidence: 97%
“…The upregulatory effect of statins on KLF2 expression has been traced to inhibition of protein prenylation and consequent inhibition of Rho activation 74 79 80. It is reasonable to suspect that modulation of KLF2 is pertinent to the reported favourable impacts of concurrent metformin or statin therapy on COVID-19 prognosis 81 82…”
Section: Sirt1/ampk Promote Induction Of Kruppel-like Factor 2 Crucia...mentioning
confidence: 99%